Radio Educational Promotion Management Strategy in Increasing Market Penetration of InformationLiteracy Programs for School Children - Miftah Amir; Fatra Syahlan; R. Edy Rachmadio; Derry Nugraha (CV. Era Digital Nusantara, 2026)
This study examines the promotional management strategies employed by educational radio stations and their impact on market penetration of information literacy programs among middle school students. Utilizing a quantitative descriptive-correlational design, data were collected from 384 students aged 12-15 years through structured questionnaires measured on a five-point Likert scale. The research operationalized promotional management strategies through four dimensions—advertising, public relations, sales promotion, and direct marketing—while market penetration was assessed through awareness, adoption, and engagement levels. Multiple linear regression analysis revealed that promotional strategies collectively explain 61.2% of variance in market penetration (R² = 0.612, F = 149.346, p < 0.001), indicating substantial predictive power. Public relations emerged as the most influential dimension (β = 0.357, p < 0.001), followed by direct marketing (β = 0.246, p < 0.001), advertising (β = 0.214, p < 0.001), and sales promotion (β = 0.198, p < 0.001). All promotional dimensions demonstrated statistically significant positive effects on market penetration. However, descriptive analysis revealed a critical awareness-to-engagement gap, with awareness scoring significantly higher (M = 3.82) than adoption (M = 3.21) and engagement (M = 3.11), indicating challenges in converting program knowledge into sustained listening behavior. The findings underscore the importance of relationship-building strategies and school partnerships over traditional advertising approaches in educational broadcasting contexts. Practical implications suggest that educational radio stations should prioritize public relations initiatives, foster institutional collaborations, and develop hybrid digital-radio formats to enhance market penetration and bridge the awareness-adoption gap. This research contributes to integrated marketing communication theory in educational media contexts and provides evidence-based recommendations for stakeholders committed to advancing information literacy among youth populations.